Pest survey card on Huanglongbing and its vectors. Issue 4 (3rd April 2019) - ; Parnell, Stephen; Camilleri, Melanie; Diakaki, Makrina; Schrader, Gritta; Vos, Sybren
Abstract : This pest survey card was prepared in the context of the EFSA mandate on plant pest surveillance (M‐2017‐0137), upon request by the European Commission. The purpose of this document is to assist the Member States in planning annual survey activities of quarantine organisms using a statistically sound and risk‐based pest survey approach, in line with the current international standards. The data requirements for such activity include the pest distribution, its host range, its biology, risk factors as well as available detection and identification methods. This document is part of a toolkit that consists of pest‐specific documents, such as the pest survey cards and generic documents relevant for all pests to be surveyed, including, the general survey guidelines and statistical software such as RiBESS+